2001
DOI: 10.2486/indhealth.39.250
|View full text |Cite
|
Sign up to set email alerts
|

Long Working Hours and Subjective Fatigue Symptoms.

Abstract: Presuming that overtime work may associate with chronic fatigue and then decrease cardiovascular function, this report was prepared to find out the definite positive relationship between long working hours and subjective fatigue complaints. We analysed the data of a field survey of 238 men who were working at the department of research & development of three electronics manufacturing companies in S. Korea. The field survey consisted of self-report questionnaires on the working hours, health conditions, and fat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
82
1
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 105 publications
(94 citation statements)
references
References 4 publications
6
82
1
2
Order By: Relevance
“…8,14 -16,34 In addition, a number of studies have also shown that long work hours lead to disability retirement 35 and are related to selfreported physical health problems and fatigue, 36 as well as increased rates of accidents and injuries at work. 9,37,38 This study also shows a statistically significant occupational variation in self-reported hypertension. The pattern of professionals having a lower prevalence of hypertension than that of clerical and unskilled workers is consistent with other studies, which suggests that occupations requiring more challenging and mentally active work may have a protective effect against hypertension.…”
Section: Discussionmentioning
confidence: 68%
“…8,14 -16,34 In addition, a number of studies have also shown that long work hours lead to disability retirement 35 and are related to selfreported physical health problems and fatigue, 36 as well as increased rates of accidents and injuries at work. 9,37,38 This study also shows a statistically significant occupational variation in self-reported hypertension. The pattern of professionals having a lower prevalence of hypertension than that of clerical and unskilled workers is consistent with other studies, which suggests that occupations requiring more challenging and mentally active work may have a protective effect against hypertension.…”
Section: Discussionmentioning
confidence: 68%
“…In addition to traditional risk factors, occupational factors should also be considered. In previous studies, shorter sleep duration has been associated with longer working hours (9)(10)(11)(12)(13). Shift work induces sleep problems (25).…”
Section: Discussionmentioning
confidence: 99%
“…More importantly, the majority of the relevant previous studies were conducted in populations comprising a broad age range, including young, middle-aged, and elderly people, who may have had different confounding effects on the true relationship. Among elderly individuals, health status, including underlying diseases, strongly influences sleep duration (8), whereas among young and middle-aged individuals, sleep duration depends significantly on occupational factors including working hours (9)(10)(11)(12)(13). Since occupational factors may confound the true association between sleep duration and cardiovascular events among middle-age individuals, occupational factors should be considered in the determination of the relationship between cardiovascular events and sleep duration.…”
mentioning
confidence: 99%
“…However there are some data from questionnaire studies indicating greater fatigue in relation to overtime work (Hayashi et al, 1996;Park et al, 2001;Proctor et al, 1996). A questionnaire study by Park et al (2001) found that the group with a greater number of work hours per week reported more fatigue before going to work than those with shorter hours. Proctor et al (1996) carried out one of the few studies that have employed cognitive measures.…”
Section: Overtime Work and Long Hours In Relation To Sleep Fatigue Amentioning
confidence: 99%